Field manual for water quality monitoring an environmental education programfor schools / Mark K. Mitchell, William B. Stapp - Mitchell, Mark K. [et.al] (Michigan: Thompson-Shore Inc, 1988)
The River and its watershed, dissolved oxyge, the meaninig and procedures of nine water quality tests, using the weighting curve charts and water quality indez, calculating the results, benthic macroinvertebrates, a case study, orientation to the three communities, the interactive Rouge river water quality project
Table of contents, preface, literature cited
Col. Agro
Keywords: 1. NATURAL RESOURCES 2. FIELD-MANUAL-MONITORING OF WATER QUALITY 3. ENVIRONMENTAL EDUCATION 4. SCHOOL PROGRAMS 5. EDUCATION